2D Silicate Materials for Composite Polymer Electrolytes. Issue 19 (21st August 2021) - Tang, Hui; Sun, Mingxuan; Wang, Chengliang
Abstract: Two‐dimensional (2D) silicate materials have become one of the promising candidates for constructing composite polymer electrolytes due to their advantages of low cost, high stability, good mechanical property, high ionic conductivity and potential to inhibit the growth of lithium dendrites. However, the application of 2D silicate materials in composite polymer electrolytes (CPEs) is still at the infancy stage and facing a lot of challenges. In this minireview, we summarize the structures and properties of 2D silicate materials that have been applied in CPEs, the processing methods of composite electrolytes based on 2D silicates, and the recent process of 2D silicate materials in CPEs. We hope this review could present a general overview of the 2D silicates for CPEs and promote the further study for potential applications. Abstract : Two‐dimensional (2D) silicate materials have become one of the promising candidates for constructing composite polymer electrolytes (CPEs). However, their application in CPEs is still at the infancy stage and facing a lot of challenges. The recent process of 2D silicate materials in CPEs is summarized.